MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN MELALUI PERMAINAN RODA PUTAR PADA ANAK USIA 4-5 TAHUN DI TK AN NAMIROH 4 KOTA PEKANBARU - Susilawati Susilawati; Tri Umari; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on observations in kindergarten An Namiroh 4 Pekanbaru, researchers found obstacles in children aged 4-5 years related to the ability to know the number. Therefore, to improve the ability to know the number of children in kindergarten approach is to use the media to draw concrete with the game wheel. Game wheel is used as a medium to facilitate learning in children recognize numbers 1-10. The purpose of this study was to determine how to implement the game wheel so as to improve the ability to know the number of children aged 4-5 years and the increase in the ability to know the number of games with a wheel in children aged 4-5 years. This type of research is a classroom action research conducted in two (2) cycles. Data collection tools were used in this study is in the form of observation. The number of samples in the study sample was 15 children ranging from 8 samples-sex male and 7 were female. Based showed increased ability to know the number of children aged 4-5 years through the game wheel. Improvement of pre-cycle to the first cycle of 16.11% with undeveloped category (B), an increase from the first cycle to the second cycle of 69.88% with a category Growing Perfect Hope (BSH), and an increase of up to pre-cycle second cycle of 97.24% Growing in accordance with the category of Good Hope (BSH). This indicates that the application of the game wheel in improving the ability to know the number of children aged 4-5 years in kindergarten An Namiroh 4 Pekanbaru significantly.Keywords : Symbol Number, Learning Media, Game Wheel Play